Recombinant protein Ag85B-Rv2660c-MPT70 promotes quality of BCG-induced immune response against Mycobacterium tuberculosis H37Ra - Ouyang, Jiangshan; Guo, Shaohua; Hu, Zhiming; Cao, Ting; Mou, Jun; Gu, Xinxia; Huang, Chunxu; Liu, Jie (Frontiers in Immunology, 2025)
IntroductionBacillus Calmette-Guérin (BCG), the only licensed vaccine against Mycobacterium tuberculosis (Mtb) infection, has been extensively used worldwide for over 100 years, but the epidemic of tuberculosis (TB) remains a major challenge to human health and well-being. The quest for a more effective vaccination strategy against the Mtb infection continues. Boosting the protective immunity induced by BCG with recombinant protein is a feasible approach to improve the efficacy of BCG, due to the proven safety and effectiveness of recombinant proteins as vaccination regimes against a variety of infectious diseases. While being shown to be promising in clinical trials in preventing Mtb infection, data suggest this strategy requires further improvement.MethodsIn this study, we developed a novel fusion of proteins derived from major antigenic components of Mtb, including Ag85B, Rv2660c, and MPT70 (ARM), and assessed its antigenicity and ability to boost BCG efficacy in a murine model.ResultsThe results demonstrated that the ARM immunization induced antigen-specific T and B cell responses and reduced the Mtb H37Ra burdens in the lungs and spleen. Mice that were primed with BCG and boosted with the ARM mounted a Th1-type immune response, characterized by an increased proportion of multi-functional ARM- and Mtb lysate-specific CD4+ T cells that produced IFN-γ, TNF-α, and IL-2 compared to BCG alone, and reduced the Mtb burden without the development of severe lung pathological inflammation.DiscussionThe results of our study demonstrate that the ARM boost improves the quality of the BCG-induced immune response, increases its potency of pathogen reduction, and offers an additional option for enhancing the efficacy of BCG vaccination.